What is the motor vehicle crash risk for drivers with a sleep disorder?. (October 2022) - Charlton, Judith L.; Di Stefano, Marilyn; Dimech-Betancourt, Bleydy; Aburumman, Mohammed; Osborne, Rachel; Peiris, Sujanie; Cross, Suzanne L.; Williams, Gabrielle; Stephens, Amanda; McInnes, Aaron; Odell, Morris; Darzins, Peteris; et al.
Highlights: Systematic review conducted to establish the crash risk for drivers with sleep disorders. 39 studies met the inclusion criteria, with 14 published in the last decade. 18 of the 27 studies investigating MVC risk associated with sleep apnoea reported an increased risk, 7 reported no difference, and 2 two provided inconclusive findings. All 5 studies investigating MVC risk associated with disorders of hypersomnolence and narcolepsy reported an increased risk. Only two studies investigated MVC risk associated with insomnia, with inconsistent findings. Weight of evidence suggests a moderately elevated MVC risk for drivers with sleep disorders (sleep apnoea; hypersomnia and narcolepsy), and lower risk with treatment. Abstract: In many parts of the world, drivers with serious sleep disorders have restrictions on their licence – with the fitness-to-drive criteria varying across licensing jurisdictions. This study aimed to systematically review the literature that evaluated the available scientific evidence for the relationship between sleep disorders and two driving safety outcome measures: (i) motor vehicle crashes (MVC) and (ii) on-road driving test outcome. This review was registered with PROSPERO in July 2019 (see CRD42019144643). A systematic search of public health, psychology and transport databases was conducted on November 8th, 2019. The quality of evidence for each study was rated using the National Heart, Lung and Blood Institute Quality Assessment tools. Thirty-nine studies published between 1976 and 2015 met the inclusion criteria (n = 9 case-control; n = 24 cohort/cross-sectional; n = 6 before-after). Overall, the quality of evidence for 22 studies was rated as 'good', nine as 'fair' and eight as 'poor'. Included studies addressed: sleep apnoea and sleep-related breathing disorders (n = 35); central disorders of hypersomnolence and narcolepsy (n = 5), and insomnia (n = 2), with some studies covering multiple sleep disorders. Of the thirty-five studies specifically investigating MVC risk associated with sleep apnoea, eighteen studies reported an increased risk (n = 11 'good', n = 4 'fair', n = 3 'poor' quality), seven reported no difference in risk (n = 3 'good', n = 4 'fair' quality), and two provided inconclusive findings (n = 1 'good', n = 1 'fair' quality). Most studies suggested that increased sleep apnoea severity was associated with an increased MVC risk. Furthermore, untreated sleep apnoea was predominantly associated with increased risk, whilst decreased risk was associated with Continuous Positive Airway Pressure (CPAP) and uvulopalatopharyngoplasty (UPPP) treatments. Five studies (n = 3 'good', n = 2 'fair' quality) investigated MVC risk associated with disorders of hypersomnolence and narcolepsy, and all reported increased risk. Only two studies investigated MVC risk associated with insomnia, with inconsistent findings: one reporting increased MVC risk ('good') and one reporting no difference ('fair'). Regarding impacts on on-road driving test outcome, our comprehensive search found no studies investigating the association between sleep disorders and this driving safety outcome measure. Notwithstanding the limitations of the included studies, the weight of evidence suggests a moderately elevated MVC risk for drivers with sleep disorders (sleep apnoea; hypersomnia and narcolepsy), with the majority reporting around two and a half times higher risk, and lower risk with treatment. This evidence is consistent with current fitness-to-drive guidelines, most of which specify licence restrictions conditional upon severity, treatment compliance and effective response to treatment. The generalisability of the findings is limited as many identified studies had methodological limitations, were conducted across a wide time period, in numerous licensing jurisdictions with different requirements, and across a diverse range of participant populations. A large-scale, population-based controlled study, in multiple licensing jurisdictions with equivalent licensing and fitness-to-drive requirements, is warranted to rigorously investigate MVC risk and sleep disorders, including evaluating the possible benefit of therapies.